2017
DOI: 10.1371/journal.pone.0169140
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Devices to Monitor Biofouling and Metals Deposition on Plumbing Materials Exposed to a Full-Scale Drinking Water Distribution System

Abstract: A Modified Robbins Device (MRD) was installed in a full-scale water distribution system to investigate biofouling and metal depositions on concrete, high-density polyethylene (HDPE) and stainless steel surfaces. Bulk water monitoring and a KIWA monitor (with glass media) were used to offline monitor biofilm development on pipe wall surfaces. Results indicated that adenosine triphosphate (ATP) and metal concentrations on coupons increased with time. However, bacterial diversities decreased. There was a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
(63 reference statements)
0
20
0
Order By: Relevance
“…No studies were found regarding heavy metals present in HDPE and PEX piping. A growing amount of evidence shows that plastic water distribution pipes can accumulate heavy metal scales (Figure 1) (Lytle et al, 2004;Cerrato et al, 2006;Campbell et al 2008;Friedman et al, 2010;Ginige et al, 2017), but no investigations were found that examined plastic building plumbing. In a survey of 15 U.S. water utilities, a wide range loadings of As (1,416 to 13,650 µg/g), Ca (4,455 to 57,790 µg/g), Fe (14,420 to 77,030 µg/g), and Pb (210 to 9,681 µg/g) were detected on PVC water distribution pipes (Lytle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…No studies were found regarding heavy metals present in HDPE and PEX piping. A growing amount of evidence shows that plastic water distribution pipes can accumulate heavy metal scales (Figure 1) (Lytle et al, 2004;Cerrato et al, 2006;Campbell et al 2008;Friedman et al, 2010;Ginige et al, 2017), but no investigations were found that examined plastic building plumbing. In a survey of 15 U.S. water utilities, a wide range loadings of As (1,416 to 13,650 µg/g), Ca (4,455 to 57,790 µg/g), Fe (14,420 to 77,030 µg/g), and Pb (210 to 9,681 µg/g) were detected on PVC water distribution pipes (Lytle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ramage et al [140] employed an RO reactor to grow C. albicans on PMMA. Ginige et al [141] installed a modified RO reactor in a full-scale water distribution system to investigate biofouling on a high-density polyethylene surface.…”
Section: In Vitro Methods To Culture Biofilm On Anti-biofilm Polymmentioning
confidence: 99%
“…device was installed in a full-scale water distribution system to investigate biofouling and metal depositions on concrete, high-density polyethylene (HDPE) and stainless steel surfaces (Ginige et al, 2017). There was a positive correlation between increase of ATP and metal deposition on pipe surfaces of stainless steel and HDPE and no correlation was observed on concrete and glass surfaces.…”
Section: Health Risk Assessments a Modified Robbinsmentioning
confidence: 99%